Japanese encephalitis virus: Associated immune response and recent progress in vaccine development. (November 2019) - Kumar, Awanish; Sharma, Praveen; Shukla, Kamla Kant; Misra, Sanjeev; Nyati, Kishan Kumar
Abstract: Japanese encephalitis (JE) has emerged as one of the most important form of viral encephalitis, which accounts for an estimated 70, 000 cases each year with approximately 10, 000 fatalities. The clinical presentations and outcome of the infection is dependent upon both virulence of viral determinants and host immune responses. The causative pathogen of JE is a virus known as Japanese encephalitis virus (JEV), which penetrates into the CNS from blood and triggers rapid humoral and cell-mediated immune response. Humoral response is crucial for the control of dissemination of JEV infection and the cytokines produced by cell-mediated immunity during JEV infections serve as potent immune mediators. Till date, JE is only vaccine preventable and no complete antiviral treatment is available so far. Further, vaccine-mediated prevention also has certain limitations. Therefore, an understanding of the pathogenesis of JEV infection can enable the researchers to presume the depth of treatment regime. This review highlights the importance of understanding of the immune mechanisms that are operated in the host during JEV infection and would be helpful in improving future vaccination strategy against JEV. Highlights: Japanese encephalitis (JE) is the main cause of viral encephalitis worldwide. Majorities of Asian and pacific countries are endemic for the disease in which more than three billion people are at risks of infection. JE virus has complex eco-epidemiology, which limits the effectiveness of vector control strategies. Vaccination is the more effective to prevent the infection where JEV is a major public health problem.